A molecular electron density theory study of the participation of tetrazines in aza-Diels–Alder reactions. Issue 26 (21st April 2020) - Domingo, Luis R.; Ríos-Gutiérrez, Mar; Pérez, Patricia
Abstract : The electron-withdrawing substituents on the tetrazine favour aza-Diels–Alder reactions towards nucleophilic ethylenes, but they do not react with electrophilic ethylenes. Abstract : The reactions of eight tetrazines of increased electrophilic character with nucleophilic tetramethyl ethylene (TME) and with electrophilic tetracyanoethylene (TCE) have been studied using Molecular Electron Density Theory. These reactions are domino processes comprising an aza-Diels–Alder (ADA) reaction followed by an extrusion of molecular nitrogen, yielding a dihydropyridazine. Analysis of the conceptual DFT (CDFT) indices showed an increase of the electrophilicity and a decrease of the nucleophilicity of tetrazines with an increase of the electron-withdrawing character of the substituent. A very good correlation between the global electron density transfer at the transition structures and the activation enthalpies for the ADA reactions involving TME was found. However, tetrazines have no tendency to react with electrophilic ethylenes such as TCE. Bonding Evolution Theory (BET) analysis of the ADA reaction of dinitro tetrazine with TME showed that the activation energy is mainly associated with the continuous depopulation of the C–C and C–N double bonds.